A 10-year update: national survey questionnaire of obstetric anesthesia units in Israel. (May 2019) - Shatalin, D.; Weiniger, C.F.; Buchman, I.; Ginosar, Y.; Orbach-Zinger, S.; Ioscovich, A.
Highlights: Prospective survey questionnaire of all 25 unit directors of obstetric anesthesia in Israel. Nineteen (76%) labor units surveyed have dedicated anesthesiologist cover. No additional labor units have opened since 2007. Large increases in delivery volume have occurred in many units. Abstract: Background: This nationwide survey was conducted to provide data about the obstetric anesthesia services in Israeli labor and delivery units in 2016. Methods: Prospective survey questionnaire was emailed to obstetric anesthesia unit directors/chairperson of all 25 labor and delivery services units within the jurisdiction of the Israeli Ministry of Health. Results: The response rate was 100%. Nineteen (76%) units have dedicated anesthesiologist cover. Fifteen (60%) units offered nitrous oxide, four units (16%) offered patient-controlled intravenous fentanyl and six units (24%) offered patient-controlled intravenous remifentanil for alternative labor analgesia. The median (range) epidural rate was 60% (22–85%). The median (range) cesarean delivery rate was 20% (10–26%). Overall, general anesthesia was performed for median (range) 10% (1–25%) of cesarean deliveries. Neuraxial anesthesia was performed for 95% (40–99%) of elective and 60% (0–90%) of urgent cesarean deliveries. Intrathecal morphine was administered routinely for spinal anesthesia for post-cesarean delivery analgesia in 11 (44%) units. Nineteen (72%) units had a written aspiration prophylaxis protocol; 20 (80%) had a written labor analgesia protocol; 19 (76%) had a postdural puncture headache management protocol; 20 (80%) had a local anesthetic toxicity protocol; 24 units had Intralipid available in the unit. Conclusion: No new labor units have opened since 2005, despite huge increases in delivery volume in many units. These units manage increased numbers of epidurals and cesarean deliveries. Use of intrathecal morphine for spinal anesthesia has become more widespread. Future efforts should focus on availability of emergency equipment, separate obstetric anesthesia staffing, and establishing emergency protocols.